Pengujian Tungku Pembakar Sampah Minim Asap - Andhi Akhmad Ismail; I Aris Hendaryanto; Budi Basuki (Jurnal Engine: Energi, Manufaktur, dan Material, 2025)
Waste refers to residual materials resulting from various human daily activities or natural processes that exist in solid form. In general, the term waste denotes unwanted materials or substances considered to have lost their usefulness after a certain activity or domestic process has been completed. To date, waste management efforts in many regions have not yet achieved optimal results. The level of public awareness and concern regarding environmental issues related to waste also varies significantly, making this issue an urgent environmental challenge that requires immediate attention and solutions. This study focuses on testing the effectiveness of waste treatment methods through the combustion process. The main objective is to determine the concentration levels of carbon monoxide (CO) and other hazardous gases generated during combustion, as well as to evaluate the performance of a waste incineration machine designed to produce low-smoke emissions. Gas concentration measurements were conducted using gas detection sensors integrated with an Arduino-based microcontroller system. The research approach combines both qualitative and quantitative methods. The qualitative aspect involves reviewing and comparing previous research findings, while the quantitative approach is carried out through direct measurements using a self-designed measuring instrument. This study is part of an ongoing research program aimed at developing a Low-Smoke Waste Incinerator Machine. Preliminary results indicate that the effectiveness level of the waste incinerator remains relatively low. This condition is attributed to the high concentrations of harmful exhaust gases such as carbon monoxide (CO), nitrogen oxides (NOx), and sulfur dioxide (SO₂) produced during the combustion process. In addition, the design of the incinerator has not yet reached optimal efficiency, as reflected by the persistently high NOx and SO₂ emissions. Therefore, more precise calibration of the gas sensors is required to ensure that the measurement data obtained accurately represent the actual concentrations of combustion gases.